(untitled) (Third Sector Social Economic Review, 2020)
The Smart City is nowadays seen like a key strategy to improve the quality of life of billions of people living in cities all over the world. Number of cities transformed to smart cities has been remarkably increasing. When all urban areas like cities, towns in a country become smart, whole country can be called smart country. The fundamental idea behind smart country performance measurement is that as a result of increasing number of smart cities being the intersection point of growing urbanization and developing technology, smart cities need to be integrated and managed on higher level by being considered from smart country perspective. As a forward-thinking smart country concept is going to become more important and smartness level of countries needs to be classified and measured. In the present paper smart country performance scores and main dimension scores of Switzerland, Bosnia and Turkey are compared and presentented. Moreover Turkey’s smart country performance is analysed and potential improvement areas for the current state are presented.